Tanggung Jawab Pt Pegadaian Terhadap Nasabah Saat Barang Jaminan Di Lelang Menurut Kuhperdata (Studi Kasus Di Pt Pegadaian Namosain Kupang) - Alfaradie Boleng Metha; Siti Ramlah Usman; Yossie M Y Jacob (Law Faculty, Nusa Cendana University, 2026)
This study examines the responsibility of PT Pegadaian towards customer collateral when an auction occurs according to the Civil Code at PT Pegadaian UPC (Branch Service Unit) Namosain, Alak District, Kupang City. This study uses an empirical legal research method with a statutory approach and a conceptual approach. Data were obtained through observation, interviews, and literature studies. The results of this study indicate that (1) the pawnshop is responsible for carrying out the auction starting from the maintenance and storage of collateral and notification to customers that their credit is due until the auction notification. In addition, the form of responsibility of the pawnshop parties will provide the remaining auction proceeds to customers at PT. Pegadaian UPC (Branch Service Unit) Namosain, namely by handing over the remaining auction money to customers directly. (2) the legal consequence is that customers will lose their rights to their goods, where the pawnshop has the right to conduct an auction to pay off unpaid loans and other administrative costs, but customers still have the right to receive the remaining auction proceeds if there is an excess. Therefore, it is important for customers to read and understand the pawn provisions so as not to suffer losses due to lack of information.